2022
DOI: 10.3390/su14031479
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Evaporative Cooling Assisted Solid Desiccant Dehumidification System for Agricultural Storage Application

Abstract: The study aims to investigate Maisotsenko cycle evaporative cooling assisted solid desiccant air-conditioning (M-DAC) system for agricultural storage application. Conventional air-conditioning (AC) systems used for this application are refrigeration-based which are expensive as they consume excessive amount of primary-energy. In this regard, the study developed a lab-scale solid silica gel-based desiccant AC (DAC) system. Thermodynamic performance of the developed system was investigated using various adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Figure 1 shows CC's impact on the agriculture sector and climate-smart adaptation strategies. Among various subsectors of agriculture, the crop sector is an important subsector that contributes about 4.41% to the GDP of the country and ensures food security for a rapidly growing population [1,10]. The Climate change impacts on agriculture sector with associated climate-smart adaptation strategies [9].…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%
“…Figure 1 shows CC's impact on the agriculture sector and climate-smart adaptation strategies. Among various subsectors of agriculture, the crop sector is an important subsector that contributes about 4.41% to the GDP of the country and ensures food security for a rapidly growing population [1,10]. The Climate change impacts on agriculture sector with associated climate-smart adaptation strategies [9].…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%
“…For instance, the agriculture sector mainly relies on adequate supplies of water and energy. Agriculture consumes 70% of the global scale freshwater withdrawals for the growth of agriculture commodities [5,6]. However, it has been identified that the freshwater reserves are shrinking due to climate change consequently impacting the agri-food supply chain thereby exploring alternative solutions such as desalination [7,8].…”
Section: Introductionmentioning
confidence: 99%